Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Higa Sugashima, Jorge Takeshi (2018)
This paper aims to propose a strategic plan for the corporation's entry into the Peruvian market. To this end, internal and external factors were analyzed to determine strategies that would allow it to compete with brands already positioned (Zara, H&M and Forever 21) in the Fast Fashion industry. Fast Retaling is among the three best in the Fast Fashion industry worldwide, its SPA business model (retailer of specialized store of own brand) allows a good quality of products, constant innovation in production and provide solutions to customers. It is an economically strong group and has the experience of entering new markets (United States and China; the strongest). Peru is a politically unstable country; however it has a strong economy, which allows it not to have high variations in exchange rate and its currency is one of the best valued in the region. Socially its consumers; thanks to globalization, they are in search of new and better alternatives of consumption. The provinces grow constantly year after year with the arrival of new commercial centers; being an opportunity for the Fast Fashion sector, as for the technological factor the social networks, are a great alternative for the promotion of products due to the reach and engagement that they have in the Peruvians. The results recommend Fast Retailing to enter the Peruvian market with the UNIQLO brand, the most recognized worldwide to be able to face the strong competition that has already settled in the country. The high demand for products in the Fast Fashion sector and the stable economy make Peru a recommendable country to invest in.